Pengaruh Girl Group Twice sebagai Brand Ambassador Scarlett Whitening terhadap Keputusan Pembelian Konsumen melalui Mediasi Brand Image - Naufal Al Hamid; Rumyeni Rumyeni (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2024)
Scarlett Whitening is one of the beauty companies that takes marketing strategy steps by utilizing the presence of brand ambassadors, such as the girl group Twice. This study aims to analyze the influence of Twice brand ambassadors and brand image on consumer purchasing decisions for Scarlett Whitening in Pekanbaru. The research method used is quantitative with an explanatory approach and a questionnaire as an instrument in data collection. The population in this study were consumers of Scarlett Whitening beauty products whose numbers were unknown and the sample was obtained as many as 272 respondents. The results of this study indicate that (1) brand ambassadors partially influence purchasing decisions, (2) brand image partially influences purchasing decisions, and (3) brand ambassadors and brand image simultaneously influence purchasing decisions with an effect of 43.1%. It is concluded that in improving purchasing decisions, companies can consider using the right brand ambassadors who have good credibility and pay attention to brand image and consumer needs.